The Influence of Individual Characteristics and Employee Loyalty on The Performance of Police Sector Employees New Attack - Heru Abdullah; Zulkifli Rangkuti; Eddy Hermawan Hasudungan Panjaitan (Dinasti Publisher, 2026)
The purpose of this study is to describe and analyze the influence of individual characteristics on employee performance, the influence of employee loyalty on employee performance, and the simultaneous influence of individual characteristics and employee loyalty on employee performance in the Serang Baru Sector Police, there is an influence of individual characteristics on employee performance. It is proven that the t-count value for variable X1 (individual characteristics) is 4.786 while the t-table value for n = 54 is 2.005, There is an influence of employee loyalty on employee performance. It is proven that the t-count value for variable X2 (employee loyalty) is 9.693, while the t-table value for n = 54 is 2.005. The R Square value is 0.805. This indicates that 80.5% of individual characteristics (X1) and employee loyalty (X2) jointly influence employee performance (Y), while the remaining 19.5% is influenced by other factors not examined in this study.